Estimation the Presence of Heavy Metals and Trace Elements in Indian Herbal Cosmetics by Atomic Absorption Spectrophotometer - Chakraborty, Krishnasis; Chaudhary, Suraj (Asian Journal of Pharmaceutical Research and Development, 2019)
Heavy metals are identically Pb, Cd and micronutrients elements like Ca, Mg, Al, Cu and Zn were quantitatively estimated using Flame Atomic Absorption Spectrometry (FAAS). Similarly, heavy metals such as As and Hg were quantitatively estimated by Hydride Generation Technique i.e. Cold Vapor Atomic Absorption Spectrometry method expending nitrogen as carrier gas in 30 herbal cosmetic preparations available in Indian markets. The results designate that among the toxic heavy metals. In the present study, Arsenic was found significantly well below the permissible limit, but Cd was found above the permissible limit in the all samples. Trace elements like Ca and Mg were found in higher amount than compare to Al, Cu, and Zn. Presence of trace elements can corroborate to be beneficial but existence of toxic heavy metals in such amounts certainly has adverse effects on the consumer health who always take the herbal products in an impression of being safe because of the natural origin. In conclusion, execution of strict and isolated regulatory guidelines and promotion of Good Analytical Practice (GAP), Good Manufacturing Practices (GMP) and Good Agricultural and Control Practices (GACP) is suggested for herbal cosmetics by WHO and other regulatory agencies. This study presents the status of heavy metals and trace elements in marketed herbal cosmetic formulations and provides a simple and convenient AAS method which can effectively be adopted at Industrial level for the quality control and standardization of herbal cosmetic preparations and other related products.